Avascular Necrosis of Femoral Head as the Initial Manifestation of CML. (1st September 2014) - Kumar, Suresh; Bansal, Deepak; Prakash, Mahesh; Sharma, Prashant
<x xml:space="preserve">Abstract</x> Summary: A 12-year-old female is reported who presented with right hip pain for 6 months. With massive splenohepatomegaly and leukocytosis, CML was suspected and confirmed on bone-marrow examination and cytogenetics. Further investigations confirmed avascular necrosis (AVN) of the right femoral head. CML was treated by hydroxyurea, followed by imatinib. AVN was managed conservatively; patient demonstrated progressive improvement, though a mild limp in the gait was persisting at 22 months. AVN as the initial manifestation of CML is a rarity. Leukostasis is considered to be the pathophysiological mechanism. In view of the rarity, a case is reported, along with compilation of previously reported cases.